(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2025)
This paper aims to explore the attitudes of hospitality industry students towards the significance of cultural elements and Intercultural Communicative Competence (ICC). It also examines the necessity of incorporating cultural elements into English for Specific Purposes (ESP) curriculum and assesses the intercultural sensitivity of the students of the College of Hotel Management in Belgrade. ICC is crucial for effective business communication in the hospitality sector. Therefore, the research seeks to enhance ESP curriculum by considering students’ attitudes and needs related to ICC in a business setting. The survey results indicate that students are interested in integrating cultural elements into ESP course and recognize the importance of intercultural aspects. Additionally, they tend to adopt an ethnorelativistic perspective towards other cultures. Improving the curriculum to emphasize intercultural competence can better prepare students for the challenges they will face in their future careers.